Combating the corporate paper war: optimising electronic mail and electronic filing - Bothma, Marchelle Marelize (My University, 2006)
The primary objective of this research project was primarily to investigate filing methods and mailing practices in the computer support or administrative environment with specific focus on the abuse of paper. The research design consisted of an exploratory investigation in selected Higher Education Institutions in the Province of Gauteng whereby a structured questionnaire was used as a measuring instrument. The investigation was sub-divided into two categories, namely, paper-based filing systems and mailing systems as opposed to electronic filing and mailing systems. In the empirical findings, analysis and interpretations, correlation and cross-tabulation were done on all sets of variables in order to determine whether any meaningful associations could be found. With reference to the title of this study "Combating the corporate paper war: optimising electronic mail and electronic filing", it has been proven that the war against paper abuse is far from over. Perceptions regarding a future paperless office and assumptions that technology such as the electronic mail facility and electronic filing could assist organisations to combat paper abuse were unfounded, due to a lack of guidance and control measures in the corporate environment. Consequently, it is recommended that an e-filing and e-mailing model be created and followed in conjunction with specified computer software features in order to counteract the abuse of paper. Follow-up research could focus on electronic filing methods versus scanning of documents for filing purposes.
Thesis (M. Tech. (Office management & Technology)) -- Vaal University of Technology
Keywords: Filing methods; Electronic filing; Paper abuse; 651.8; Business -- Data processing.; Electronic mail systems; Electronic filing systems; Office management -- Data processing